Media Pembelajaran Interactive White Board Dalam Meningkatkan Motivasi Belajar Bahasa Arab Mahasiswa - Khoirunnisa'il Fitriyah; Utin Mutammiroh (LP3M IAI Al Urwatul Wutsqo Jombang, 2025)
This study aimed to examine the effectiveness of using an Interactive Whiteboard (IWB) as a learning medium in enhancing the motivation to learn Arabic among students at STAI Sabilul Muttaqin Mojokerto. A qualitative descriptive approach was employed in this study, with data collected through observations, in-depth interviews, and documentation. The results showed that the use of IWB significantly increased students' motivation to learn, as demonstrated by four main indicators: (1) Attention, which showed an increase in focus and interest during lessons; (2) Relevance, where the material was more easily understood due to its connection to real-life contexts; (3) Confidence, where students became more active and willing to participate in the learning process; and (4) Satisfaction, where students expressed a sense of enjoyment and fulfillment in their learning experiences. These findings suggest that IWB can be an effective and innovative alternative in Arabic language learning at higher education institutions, especially in creating an interactive, engaging, and motivating learning environment.